Sustainable Development Issues in Chemistry Learning as Educational for Sustainable Development Implementation: A Systematic Literature Review - Anggraeni, Lely; Rohaeti, Eli (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This study aims to systematically synthesize research articles on the application of Educational for Sustainable Development (ESD) in chemistry learning based on their suitability with the research theme: sustainable development issues, ESD dimensions, SDGs, and chemistry concepts. The urgency of this research is to explore the potential of sustainable development issues in chemistry concepts as an implementation of ESD to help teachers who experience difficulties in integrating sustainable development issues into chemistry concepts. This research was conducted with a systematic literature review design that synthesized 23 articles from the ERIC, Science Direct, and Google Scholar databases using the keywords